ANALISIS STRUKTUR DAN POTENSI PERDAGANGAN INDONESIA-TURKI - Aditya Paramitha Alhayat (Buletin Ilmiah Litbang Perdagangan, 2011)
since distance is considered as a barrier to trade in the contemporary world, it is perceive that all countries become important markets for exporters. For Indonesia, turkey is considered as high potential market as well as a gateway of trade and investment with its proximity to major markets such as europe, middle east and Caucasus. Therefore, this paper aims to define complementary trade structure, relations, and intensity between Indonesia and Turkey. It also identifies the sectors that have comparative advantage and potential for Indonesian products in the turkish market.this study shows that the level of trade complementarity between Indonesia and turkey are high and there is high intra-industry trade on some products. this is an important indication that stangthening trade relations may have a positive impact for both countries in the future because of mutual cooperation. In addition, indicative potential trade provides additional information about Indonesia’s export products that can be developed further related to a high demand in turkey